2003
DOI: 10.1007/s10278-003-1661-z
|View full text |Cite
|
Sign up to set email alerts
|

Soft Copy versus Hard Copy Reading in Digital Mammography

Abstract: The objective of this study was to compare soft copy reading at a mammography work station with hard copy reading of full-field digital mammographic images. Mammograms of 60 patients ( n = 29 malignant, n = 31 benign) performed with full-field digital mammography (Senographe 2000D, GE, Buc, France) were evaluated. Reading was performed based on hard copy prints (Scopix, Agfa, Leverkusen, Germany) and on 2 k x 2.5 k high-resolution monitors (Sun Ultra 60, Sun Microsystems, Palo Alto, California, USA). Four read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Some studies have evaluated the efficacy of soft-copy reading of digital mammography using a flat panel detector. Two studies have demonstrated that soft-copy reading using 5-MP CRT monitors is as accurate as hardcopy reading [19,20]. In addition, 5-MP CRT monitors and 5-MP LCDs were revealed to be equivalent for evaluating the normal anatomy and features of abnormalities, simulated masses, and microcalcifications [21,22].…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have evaluated the efficacy of soft-copy reading of digital mammography using a flat panel detector. Two studies have demonstrated that soft-copy reading using 5-MP CRT monitors is as accurate as hardcopy reading [19,20]. In addition, 5-MP CRT monitors and 5-MP LCDs were revealed to be equivalent for evaluating the normal anatomy and features of abnormalities, simulated masses, and microcalcifications [21,22].…”
Section: Discussionmentioning
confidence: 97%
“…Several investigations have shown that interpretation with soft-copy display is likely to be useful with digital mammography and is unlikely to change accuracy or speed compared with interpretation using hard-copy display of digital mammography [6,11]. This is the case despite the fact that the spatial resolution of a workstation monitor is lower than that of film for printing [12][13][14].…”
Section: Discussionmentioning
confidence: 98%
“…They strongly recommended the post-processing of images, including adjustments of window level and zoom, during soft-copy interpretation [4,5]. Obenauer et al reported that further studies of tools in soft-copy reading are needed to realize its potential benefits [6].…”
Section: Introductionmentioning
confidence: 99%
“…For rural or underserved areas, telemedicine may provide a cost-effective solution for screening mammography programs and computed radiography (CR) and full-field digital mammography (FFDM) are useful in the implementation of telemammography services. Although previous studies have reported no significant differences between film-screen mammography and digital modalities [6][7][8], this latter technology may be unaffordable for vulnerable populations, where only conventional film-screen mammograms may be available. Therefore, the digitization of films is required to provide telemammography services.…”
Section: Introductionmentioning
confidence: 82%